New Goods and the Relative Demand for Skilled Labor - Xiang, Chong (The Review of Economics and Statistics, 2005)
This paper provides data on the output and factor payments of new goods for every four-digit industry in the U.S. manufacturing sector in the late 1970s and 1980s. For the entire manufacturing sector, the new goods' average skilled-labor intensity exceeds the old goods' by over 40%, and new goods can account for approximately 30% of the increase in the relative demand for skilled labor. Because new goods provide a direct measure of technology, this paper offers new evidence that technology has shifted demand in favor of skilled labor, consistent with the technology skill-complementarity hypothesis.